2007
DOI: 10.1016/j.jcrs.2006.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Eleven-year follow-up of laser in situ keratomileusis

Abstract: Laser in situ keratomileusis was moderately predictable in the correction of high degrees of myopia. After the sixth postoperative month, refractive and topographic stability were obtained. No long-term sight-threatening complications occurred during the follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…It exceeded ±1.0 and ±2.0 D of attempted refraction in 49.25 and 19.40% of eyes. Our results are similar to those of previous studies of LASIK for high myopia which found that between 30 and 60% of eyes were within ±1.0 D after surgery [28,29,30,31,32,33,34]. Dai et al reported that SE refraction exceeded ±1.0 D of attempted refraction in 23.53% [12] and 15.38% [24] eyes with myopia ≥–6.0 D, and exceeded ±2.0 D of attempted refraction in 13.79% [12] eyes with myopia ≥–10.0 D. In the study of LASEK for high myopia by Kim et al [27], it was within ±1.00 D of attempted refraction in 71.2% of eyes.…”
Section: Discussionsupporting
confidence: 92%
“…It exceeded ±1.0 and ±2.0 D of attempted refraction in 49.25 and 19.40% of eyes. Our results are similar to those of previous studies of LASIK for high myopia which found that between 30 and 60% of eyes were within ±1.0 D after surgery [28,29,30,31,32,33,34]. Dai et al reported that SE refraction exceeded ±1.0 D of attempted refraction in 23.53% [12] and 15.38% [24] eyes with myopia ≥–6.0 D, and exceeded ±2.0 D of attempted refraction in 13.79% [12] eyes with myopia ≥–10.0 D. In the study of LASEK for high myopia by Kim et al [27], it was within ±1.00 D of attempted refraction in 71.2% of eyes.…”
Section: Discussionsupporting
confidence: 92%
“…However, a decrease in best corrected visual acuity from 1 month to 3 months occurred in BSCVA Z best spectacle-corrected visual acuity; n Z number of eyes; UCVA Z uncorrected visual acuity both groups; the decrease could be attributed to postoperative stromal remodeling and regression. 23,24 In the iris recognition group, a higher percentage of eyes (92.0%) than in the control group (85.7%) were within the G0.50 D range in SE. In terms of stability, there was a small regression of effect between 1 month and 3 months in both groups, with no significant difference over time in either group.…”
Section: Discussionmentioning
confidence: 89%
“…[2][3][4][5][6][7][8][9] Recent studies of LASIK with longterm follow-up (7 to 11 years) [10][11][12][13][14][15] report few serious complications that lead to visual deterioration. However, the rate of retreatment after LASIK remains as high as 5.5% to 27.5%, 13,14,[16][17][18][19] and most retreatments are for refractive regression, which refers to a return to a certain degree of refraction postoperatively.…”
mentioning
confidence: 99%